Determinants of investment intention in sharia stocks - Sylvania Dwi Yulianti; Salsabilla, Selfira (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose – The goal of this study is to determine the factors influencing students' intention to invest in sharia stocks using the Theory of Planned Behavior (TPB). Methodology – Quantitative approaches are used in this study. This study employs primary data by sending questionnaires online to 236 respondents who met the requirements of being students currently enrolled in Yogyakarta and possessing investment savings. The data analysis method employed is the Structural Equation Model (SEM), which uses the SmartPLS 3.0 software.Findings – The findings demonstrated a significant positive relationship between the intention to invest in sharia stocks and the factors of financial literacy, investor personality traits, attitudes, financial efficacy, and Islamic religiosity. On the other hand, the intention to invest in Islamic stocks is unaffected by a subjective norm.Implications – These results will be helpful for financial service providers to be able to choose the best marketing approach to attract more customers. In addition, it assists the lecturer to be able to persuade Muslim students to invest in sharia stocks.Originality – Since sharia stocks must adhere to Islamic law, this study investigates the impact of Islamic religiosity on student intentions to invest in sharia stocks.